Increased Rapid Eye Movement Sleep Is Associated With a Reduced Risk of Heart Failure in Middle-Aged and Older Adults - Zhao, Binbin; Jin, Xiaoying; Yang, Jian; Ma, Qingyan; Yang, Zai; Wang, Wei; Bai, Ling; Ma, Xiancang; Yan, Bin (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Rapid eye movement (REM) sleep is closely related to all-cause mortality. The aim of this study is to explore the role of REM sleep on the incident heart failure (HF). Methods: We selected 4,490 participants (2,480 women and 2,010 men; mean age, 63.2±11.0 years) from the Sleep Heart Health Study. HF was identified as the first occurrence during a mean follow-up period of 10.9 years. REM sleep including percentage of REM sleep and total REM sleep time were monitored using in-home polysomnography at baseline. Multivariable Cox regression analysis was utilized to explore the relationship between REM sleep and HF. Results: In total, 436 (9.7%) cases of HF were observed during the entire follow-up period. After adjusting for potential covariates, an increased percentage of REM sleep (per 5%) was independently associated with a reduced incidence of HF (hazard ratio [HR] 0.88, 95% confidence interval [CI] 0.82–0.94, P<0.001). A similar result was also found between total REM sleep time (increased per 5 min) and incident HF (HR 0.97, 95% CI 0.95–0.99, P<0.001). Moreover, the fourth quartile of both percentage of REM sleep (HR 0.65, 95% CI 0.48–0.88, P=0.005) and total REM sleep time (HR 0.64, 95% CI 0.45–0.90, P=0.010) had lower risk of incident HF when compared with the first quartile. Conclusions: An increased percentage of REM sleep and total REM sleep time were associated with a reduced risk of HF. REM sleep may be a predictor of the incident HF.